Is Kelami's Method Still Useful in the Smartphone Era? The Virtual 3-Dimensional Reconstruction of Penile Curvature in Patients with Peyronie's Disease: A Pilot Study. Issue 1 (13th November 2020) - Pavone, Carlo; Abrate, Alberto; Altomare, Silvia; Vella, Marco; Serretta, Vincenzo; Simonato, Alchiede; Callieri, Marco
ABSTRACT: Background: Peyronie's disease is an idiopathic fibrotic disease affecting the penile tunica albuginea. Among other resulting deformities, the more common penile curvature should be assessed preferentially with in-office goniometric estimation after pharmacologically induced erection, although clearly invasive and uncomfortable. Aim: In the present pilot study, we investigated the usefulness for the patient and the surgeon of a 3-dimensional (3D) reconstruction of the penile curvature obtained through photogrammetry software in clinical evaluation and surgical planning. Methods: Enrolled patients received alprostadil 10 μg by intracavernous injection. Then, the medical personnel took a sequence of up to 50 photographs in orthostatism via a smartphone and processed them to obtain a 3D model of the whole groin area with 3DF Zephyr free software (3Dflow SRL, Verona, Italy), to take measurements of the penile curvature with MeshLab software (National Research Council of Italy, Rome, Italy) and to simulate the results after corporoplasty with Blender software (Blender Foundation, Amsterdam, the Netherlands). Finally, we submitted a 1–5 Likert scale to patients and surgeons investigating their satisfaction with the use of the 3D model during preoperative counseling, surgical planning, and the esthetic results after surgery. Outcomes: We investigated the patient and surgeon satisfaction with the use of the 3D model in understanding/evaluating the pathology and the surgical planning during the preoperative visit and the satisfaction with the final esthetic results in relation to the preoperative model itself. RESULTS: 4 patients were included. The median photographs acquisition and computer processing time were 39 seconds and 347.5 minutes, respectively. All the patients and surgeons involved gave a score of ≥4 to all the items investigated. Clinical implications: The 3D model of the penile curvature is very useful both to the patient and the surgeon to understand the severity of the disease and the possible surgical management. Strength & Limitations: This is a pilot study including only 4 cases, but it is the first experience in which the patients with Peyronie's disease had the possibility to see a virtual 3D model of their penile curvature and final esthetic results after corporoplasty, based on 3 freely available computer applications. CONCLUSION: Our pilot study has shown that it is possible to quickly obtain a sequence of photographs to create an accurate virtual 3D model of the penis of patients with Peyronie's disease, helping the patients and the surgeon during preoperative counseling and surgical planning.